Coupling vibration of composite pipe-in-pipe structure subjected to gas-liquid mixed transport by means of green's functions. Issue 8 (10th March 2023) - Chang, X.P.; Fan, J.M.; Qu, C.J.; Li, Y.H.
Abstract: This paper focuses on the vibration characteristics of a composite pipe-in-pipe structure subjected to gas-liquid mixed transport. Through the Laplace transform, Green's functions for the forced vibration of the pipe-in-pipe structure are obtained. The implicit-form frequency equations and the mode shapes of the structure with different boundary conditions are obtained by Green's functions. The results show that there is a mode exchange phenomenon in the composite pipe-in-pipe structure. A method to reasonably classify the frequencies of the pipe-in-pipe structure is proposed and the rationality of the method is proved by the corresponding mode shapes.